The Transition from Work Contracts to Mining Business Licenses in Indonesian Mining Law: A Critical Analysis of State Control Over Natural Resources - Abdullah Widy As-Shidiq; Rifki Yustisio; Zein Ahmad Rayhan (Education of Law Journal, 2026)
This paper analyzes the fundamental shift in Indonesia’s mining law framework from the Contract of Work system to the licensing regime, specifically the Mining Business License (IUP) and the Special Mining Business License (IUPK). Driven by the objectives of optimizing state revenue and accelerating mineral downstreaming, this study examines the underlying rationales, implementation mechanisms, and subsequent implications for the country's fiscal structure and downstreaming obligations. This study adopts a normative legal research method utilizing both statute and case approaches. The results indicate that this paradigm shift aims to strengthen state control and fiscal flexibility under the mandate of Article 33 of the Indonesian Constitution. However, the implementation of downstreaming mandates faces multidimensional regulatory, investment, environmental, and social challenges. Case studies on PT Freeport Indonesia, alongside nickel and coal downstreaming policies, illustrate the practical complexities and systemic impacts of this transition. This study concludes that successfully optimizing state revenue and achieving sustainable downstreaming requires adaptive regulatory strategies, consistent law enforcement, and comprehensive social-environmental impact management.